Work engagement and identification with organizational purpose: A study at the Federal Senate - Silva, Flavia Fernanda Ribeiro e; Paschoal, Tatiane; Coelho Junior, Francisco Antonio (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Public administration has undergone numerous transformations over the past decades. Work engagement has emerged as a central phenomenon to understand the outcomes of public servants and mechanisms for better delivery of public services to citizens. Purpose: The present research tested the impact of identification with the organizational purpose on the work engagement of Federal Senate employees in Brazil. Method: A sample of 282 participants responded to the questionnaire composed of closed-ended items. Confirmatory factor analysis and structural equation modeling were conducted. Results: It was found that identification with the organizational purpose strongly and positively influenced employee engagement. Organizational purpose proved to be an important antecedent, constituting, therefore, a central phenomenon for understanding and discussing work engagement in the public sector. Conclusions: The present study advances by stimulating the debate on the topic in the Brazilian public service, filling theoretical and empirical gaps in the field, and opening up possibilities for future investigations.